1996
DOI: 10.1128/jb.178.15.4375-4380.1996
|View full text |Cite|
|
Sign up to set email alerts
|

Bacillus subtilis spore coat assembly requires cotH gene expression

Abstract: Endospores of Bacillus subtilis are encased in a protein shell, known as the spore coat, composed of a lamella-like inner layer and an electron-dense outer layer. We report the identification and characterization of a gene, herein called cotH, located at 300؇ on the B. subtilis genetic map between two divergent cot genes, cotB and cotG. The cotH open reading frame extended for 1,086 bp and corresponded to a polypeptide of 42.8 kDa. Spores of a cotH null mutant were normally heat, lysozyme, and chloroform resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
192
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(206 citation statements)
references
References 24 publications
12
192
2
Order By: Relevance
“…Class 1 groups 28 genes, including cotH and the gerP operon (Behravan et al, 2000;Naclerio et al, 1996), whose expression is induced by 210 min and peaks at 270 min. Expression of the s K -dependent gerP operon is repressed by GerE (Behravan et al, 2000), and expression of cotH does not require GerE, although it is not presently known whether the expression of cotH is repressed by GerE or not (Naclerio et al, 1996). Class 2 groups 72 genes whose expression is also induced by 210 min, but continues to rise during the duration of the experiment, at least until 330 min (Fig.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
“…Class 1 groups 28 genes, including cotH and the gerP operon (Behravan et al, 2000;Naclerio et al, 1996), whose expression is induced by 210 min and peaks at 270 min. Expression of the s K -dependent gerP operon is repressed by GerE (Behravan et al, 2000), and expression of cotH does not require GerE, although it is not presently known whether the expression of cotH is repressed by GerE or not (Naclerio et al, 1996). Class 2 groups 72 genes whose expression is also induced by 210 min, but continues to rise during the duration of the experiment, at least until 330 min (Fig.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
“…Additionally, CotH, in conjunction with CotE, is required for efficient spore germination (Naclerio et al, 1996). Recent studies have shown that the previously observed role of CotH in the assembly of the outer coat components CotC, CotG and CotB (Naclerio et al, 1996) is to stabilize CotC (Isticato et al, 2004) and CotG, which in turn is needed for dimerization and assembly of CotB (Zilhao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the outer coat proteins are assembled on the outside of the CotE structure (Henriques & Moran, 2000;Driks, 2002). Additional proteins with morphogenetic functions are needed for coat formation: SpoVID, produced under s E control, has the dual role of directing SafA to the forming spore and maintaining the CotE ring around the forespore (Henriques & Moran, 2000;Ozin et al, 2001;Driks, 2002); CotH, produced under s K control, plays a role in the assembly of various outer coat components and in the development of the lysozyme resistance typical of the mature spore (Naclerio et al, 1996;Zilhao et al, 1999). Additionally, CotH, in conjunction with CotE, is required for efficient spore germination (Naclerio et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of pro-E to its active form, E , which occurs exclusively in the mother cell, inaugurates the program of gene expression in this compartment (19,35,44,68). The E form of RNA polymerase (E E ) directs the transcription of a heterogeneous group of genes controlling functions as diverse as engulfment (23,56,58,62), germination (49,70), cortex synthesis (2,9,14,43,52,54,60,64), and coat morphogenesis (3,18,28,49,54,60,70), as well as genes that may assist in the control of the metabolic state of the mother cell (7,8,26,37). E E also drives expression of at least two regulatory genes, spoIIID (40,62,68) and sigK (39,68).…”
mentioning
confidence: 99%